SANTONIAN-CAMPANIAN PLANKTONIC FORAMINIFERAL BIOSTRATIGRAPHY, TAXONOMY AND ISOTOPE PALEOECOLOGY. - F. Falzoni (Università degli Studi di Milano, 2012)
Current biozonations based on Santonian-Campanian (Late Cretaceous) planktonic foraminiferal bioevents do not provide a high stratigraphic resolution, when compared to other time intervals. Moreover, some of the marker species of the Tethyan biozonation show a diachronous lowest occurrence across latitudes and a restricted geographic distribution. Thus, paleoclimatic and paleoceanographic inferences are poorly constrained by biostratigraphy and, in addition, are often based on diagenetically altered material. This study is aimed to 1) improve the biostratigraphic resolution of Santonian-Campanian zonal schemes based on planktonic foraminiferal bioevents; 2) reconstruct the evolutionary history of key biostratigraphic species and revise the taxonomy of problematic groups (planispiral and globigeriniform taxa) often overlooked in the literature; 3) infer the paleoecological preferences of selected planktonic foraminiferal species based on stable isotope analyses, and 4) reconstruct the paleoclimatic context of the Santonian-Campanian time interval. The Santonian-Campanian samples analyzed in this study were selected from four different localities: 1) Tanzania - western Indian Ocean (Tanzanian Drilling Project - TDP Sites 23, 28, 32 and 35); 2) Shatsky Rise - northwestern Pacific Ocean (Ocean Drilling Program - ODP Leg 198, Hole 1210B); 3) Exmouth Plateau - eastern Indian Ocean (ODP Leg 122, Hole 762C); 4) Bottaccione section outcropping in the Umbro-Marchigian Apennines near Gubbio (Italy). Samples were prepared following the standard methodologies and considering the different lithologies. A scanning electron microscope (SEM) was used to document the species, observe and describe the wall texture of the specimens at higher magnification. Cathodoluminescence analyses on selected specimens were applied to assess the degree of wall alteration. Well-preserved specimens were finally analyzed to obtain reliable δ18O and δ13C values and provide paleotemperature estimations. Results allow description of the mid Campanian ...